The Rebeca Matte Population. The Heritage and Silenced Experiences of the Popular Sectors of Ñuñoa, Chile (1956-2023) - Rosenmann Danilo, Damián; Rivas, Alvaro (Huarte de San Juan. Geografía e Historia, 2025)
This article offers a critical examination of the traditional conceptions and management of cultural heritage in Chile, which have historically prioritized large-scale state and oligarchic projects while marginalizing the sociocultural dynamics of working-class communities within the country’s heritage protection framework. Through a historical study of the Rebeca Matte housing complex in Ñuñoa, Santiago de Chile, we reassess its history and collective memory by drawing on documentary sources, oral testimonies, and historiographical analysis. Our study explores the neighbourhood’s significance as a unique case of urban development during the 1960s, shaped by public policies and informal transformations initiated by its residents. Within the broader context of rural-to-urban migration, irregular land occupations, and the social struggle for housing, we conclude that, despite its evident historical value, the neighbourhood is not recognized as heritage housing due to its lack of the attributes established by state heritage regulations.